The influence sevices quality of last-mile delivery services on customer satisfaction in Malaysia - Tan, Wei Bin (2024)
In the dynamic landscape of last-mile delivery services, customer satisfaction stands as a critical metric for success. This study investigates the multifaceted influences of delivery, packaging, technology, accessibility and trust on customer satisfaction within the context of last-mile delivery services. Expectancy-Disconfirmation Theory and SERVQUAL model serve as the underpinning theory in this study. This study applies the quantitative research method to collect data through questionnaire surveys distributed to customers of last-mile delivery services within Kuala Lumpur context. The sampling technique applied is the convenience sampling technique in which respondents are selected based on their availability, accessibility or willingness to participate. There are 401 respondents participating in this study and the data been analyzed using SPSS. The findings underscored the pivotal role that delivery price, speed and accuracy, packaging, technological advancements, ease of accessibility and trustworthiness play in shaping the perception of service quality and subsequently influencing customer satisfaction levels. Notably, trust emerged as the most influential factor contributing towards customer satisfaction in last-mile delivery services